Hydroxypropylation of 1, 2 Galactomannan by Taguchi's L9 Orthogonal Array Design. Issue 33 (2nd September 2021) - Tyagi, Rakhi; Kumar, Vineet; Sharma, Pradeep; Nautiyal, Raman
Abstract: Hydroxypropyl guar is one of the industrially significant biopolymers. In the present study, hydroxypropylation of guar gum was investigated using Taguchi's L9 orthogonal array design of experiment. Reaction conditions were optimized to obtain higher hydroxypropyl content (%) in the derivatized sample. The optimized conditions comprised 7 mL and 0.12 g of propylene oxide and NaOH respectively, keeping the methanol: water ratio 7 : 3, and reaction time 3 h at 60 °C. The hydroxypropyl content of the derivative synthesized under optimized reaction conditions was determined as 0.830 %. The structural changes introduced by the modification were corroborated by FT‐IR, 1‐D ( 1 H, 13 C, and DEPT‐135), and 2‐D (HSQC, HMBC, and COSY) NMR spectroscopic analysis. Thermal studies of the hydroxypropyl derivatives vis a vis native guar using TGA, DSC, and DTG indicated better thermal stability of the hydroxypropyl derivative in comparison to the native guar gum. The studies demonstrate that Taguchi's L9 orthogonal array is a statistically sound approach for hydroxypropylation of guar gum involving lesser number of experiments than the conventional approach. Abstract : Optimization reaction conditions for hydroxypropylation of guar galactomannan was achieved using Taguchi's L9 orthogonal array. The derivatized products were characterized by FT‐IR, 1‐D ( 1 H, 13 C, DEPT‐35) and 2‐D (HSQC, HMBC, COSY) NMR spectroscopic methods. Hydroxypropyl guar exhibited better thermal stability and can be used for diverse industrial applications.